2021
DOI: 10.52312/jdrs.2021.79
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of metacarpophalangeal sesamoid bones of the hand in Turkish population

Abstract: Objectives: This study aims to investigate the prevalence and location of the metacarpophalangeal (MCP) sesamoid bones using computed tomography (CT) images. Patients and methods: A total of 767 hands of 735 patients (503 males, 232 females; mean age: 36.9±17.0 years; range, 18 to 105 years) obtained from picture archiving and communication system were retrospectively analyzed between January 2016 and December 2019. The sesamoid bones of MCP joints I, II, III, IV, and V were recorded. Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Sbs can be found in all the fingers, but it is most common in the MCP joint of the thumb. The current study aimed to determine the presence of Sbs ossification at the thumb MCP joint of the hand, which has been confirmed in almost all individuals (98.2%-100%) by several studies 1 , 2 , 3 , 4 , 8 , 9 , 10 , 11 , separately for girls and boys, and its relationship with puberty period.…”
Section: Introductionmentioning
confidence: 69%
See 3 more Smart Citations
“…Sbs can be found in all the fingers, but it is most common in the MCP joint of the thumb. The current study aimed to determine the presence of Sbs ossification at the thumb MCP joint of the hand, which has been confirmed in almost all individuals (98.2%-100%) by several studies 1 , 2 , 3 , 4 , 8 , 9 , 10 , 11 , separately for girls and boys, and its relationship with puberty period.…”
Section: Introductionmentioning
confidence: 69%
“…While the sesamoids of the thumb MCP joint are considered a normal skeleton part of adult humans, sesamoids of other fingers may differ 3 , 10 , 12 . Several studies in the literature have found that all adults have Sb at the thumb MCP joint 1 , 2 , 3 , 4 , 8 , 9 , 10 , 11 . Yammine 2 reported a 99.93% prevalence of Sbs on the radial side and a 99.81% prevalence on the ulnar side in a meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Double sesamoids are frequently found in the first MCP joints 2 . However, single sesamoid is seen in the other MCP joints and the thumb interphalangeal (IP) joint 3–7 . Few studies have observed sesamoids in proximal interphalangeal (PIP) joint of middle, ring and little fingers 8 .…”
Section: Introductionmentioning
confidence: 99%